Just what are we doing when we're describing AI? Harvey Sacks, the commentator machine, and the descriptive politics of the new artificial intelligence. (June 2021) - Mair, Michael; Brooker, Phillip; Dutton, William; Sormani, Philippe
In dialogue with the work of Heather Love and colleagues, this article makes use of a peculiar 'descriptive assemblage' proposed by Harvey Sacks (1963) – that of the 'commentator machine' – to open up issues of 'descriptive politics' in the field of contemporary Artificial Intelligence (AI). We do so by reviewing the gameplay of Google DeepMind's AlphaGo – an algorithm designed to outperform human players at the game of Go – with a focus on the incongruities of the much discussed, indeed (in)famous 'move 37' in a human-versus-machine challenge match in 2016 (e.g. Silver et al., 2017). Looking at move 37 in conjunction with the various layers of commentary that came to be woven around it, we explore the kinds of descriptive work involved in characterising the move, the troubles that work reveals and what we can learn about the practices and politics of description from encounters with 'New AI' applications like AlphaGo.